Belajar Rekorder Dengan Bantuan Aplikasi Whatsapp pada Pembelajaran Seni Musik Di SMP Negeri 14 Solok Selatan Pada Masa Pandemi Covid-19 - Farhan Shah Idrus; Yos Sudarman (SENDRATASIK UNP, 2020)
The problem of this research rises from the Culture and Arts instruction of music at SMP 14 South Solok which is carried out during a Covid-19 pandemic situation, so there is no face-to-face learning except for the implementation of online learning which is indirectly conducted by teachers and students. This research aims to explain the implementation of recording learning with the help of WhatsApp application in learning music at SMP Negeri 14 South Solok during the Covid-19 pandemic. This is a qualitative research using descriptive analysis approach. The research’s object was the teacher and 24 students of class VII-3 who conducted recording learning using the WA application. The learning was guided by the teacher from the school for students studying at home. The research instruments were observation, interview, and documentation study. The results of the study explain that the use of WA application for recording learning in class VII-3 students at SMP Negeri 14 South Solok has advantage and weaknesses. The advantage is the ease of using the applications in learning.  This is due to the fact that it can easily send and receive chats, photos, audio, and videos related to the subject matter. However, the weaknesses exist in the unavailability of cellphone devices, unstable internet connection, and expensive internet loads to facilitate WA usage for learning.